Numerical and experimental analysis of single tie push tests on different shapes of concrete sleepers in ballasted tracks. (August 2019) - Jing, GQ; Aela, P; Fu, H; Yin, H
The lateral displacement of sleepers is one of the key issues in railroads, which is caused by different factors such as the geometry of the ballast layer as well as the shape of the sleepers. Several methods have been proposed to improve the lateral resistance of sleepers on ballasted tracks. In this paper, a series of single tie push tests have been carried out to assess the performance of end-winged, middle-winged, and bumped sleepers on ballasted tracks with a variety of shoulder ballast widths and heights. Based on the experimental results, 500 mm and 150 mm were proposed as the optimum shoulder width and height, respectively. In addition, among the abovementioned sleepers, the EW_sleeper shows a significant increase in the total lateral resistance. Discrete element method (DEM) simulations were performed using PFC 3D to determine the optimum size of the EW_sleeper wings. It was found that using a pair of wings measuring 14 cm in length and 13 cm in width can increase the lateral resistance compared to other alternatives.